Faktor-Faktor Yang Mempengaruhi Siswa SMKN Putus Sekolah Di Kota Padang - Dessi Susanti (PAKAR Pendidikan, 2014)
This study aims to look at the effect of family factors, personal characteristics, and economics of the family SMKN dropout rate in the city of Padang. Type of research is quantitative research. The population is all SMKN Padang numbering as many as 10 SMKN, sampling techniques of the elements in this study population using total sampling, Analysis using multiple regression method. The results showed that: 1) There is a significant positive effect between family factors on dropout rates in SMKN Padang, 2) There is no significant positive effect between the personal characteristics of the dropout rate in SMKN Padang, 3) There is a significant positive influence on the economic family SMKN dropout rate in the city of Padang. This means that the greater amount of economically disadvantaged children will cause the higher the dropout rate at SMKN Padang.